2017
DOI: 10.1111/ene.13463
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐stroke physical activity is associated with fewer post‐stroke complications, lower mortality and a better long‐term outcome

Abstract: Dedicated leisure-time physical activity for at least 30 min/day, at least three times per week for more than 6 months was associated with decreased stroke severity, fewer post-stroke complications, lower mortality and better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 35 publications
(44 reference statements)
5
54
0
1
Order By: Relevance
“… 6 , 8 The potential risk factors such as sex, smoking, diabetes, and protective treatments such as statin and hypertension treatment did not influence stroke severity in this study. In similar studies with some methodological differences including the definition of PA, stroke severity assessment, or assessment time, reduced stroke severity in patients who were physically active before stroke have been shown, 7 , 9 , 10 although one study shows no effect. 11 One subcategory of PA is exercise, 21 often referred to in studies as PA with moderate to vigorous intensity, which excludes the patients performing light PA such as walking.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 6 , 8 The potential risk factors such as sex, smoking, diabetes, and protective treatments such as statin and hypertension treatment did not influence stroke severity in this study. In similar studies with some methodological differences including the definition of PA, stroke severity assessment, or assessment time, reduced stroke severity in patients who were physically active before stroke have been shown, 7 , 9 , 10 although one study shows no effect. 11 One subcategory of PA is exercise, 21 often referred to in studies as PA with moderate to vigorous intensity, which excludes the patients performing light PA such as walking.…”
Section: Discussionmentioning
confidence: 90%
“… 11 One subcategory of PA is exercise, 21 often referred to in studies as PA with moderate to vigorous intensity, which excludes the patients performing light PA such as walking. 9 , 11 However, 2 studies have shown that light PA also predicts less severe stroke. 8 , 10 Hence, PA is an intervention known to prevent stroke, and the results of this study further indicate that prestroke PA also is associated with less severe stroke.…”
Section: Discussionmentioning
confidence: 99%
“…PA is directly related to stroke risk, and is consistently linked to severity, likelihood of complications, mortality rates and functional outcomes 4 . PA can not only lower the likelihood of recurrence but also influence the level of post-stroke disablement and wellbeing 11,12 . Furthermore, PA can boost social, sensory and cognitive stimulation.…”
Section: Letter To Editorsmentioning
confidence: 99%
“…Stroke remains the most common problem for neurologists to diagnose and treat . Preventative measures, such as control of hypertension, reduction in smoking and treatment of hyperlipidaemia, have made a significant contribution to preventing and delaying stroke onset.…”
mentioning
confidence: 99%
“…Other environmental factors play important roles in modifying stroke risk. For instance, a Taiwanese study showed that those that undertook >30 min physical activity three times per week or more had fewer complications and better outcomes following stroke . This could be a consequence of a parallel association with less obesity, hypertension, diabetes, smoking, etc.…”
mentioning
confidence: 99%